Screening of Phosphate-Resolving Bacteria in Rhizosphere of Cold Sunflower and Physiological and Biochemical Study. Issue 1 (June 2020) - Ba, Huifen; Jiang, Huimin; Shen, Penglin; Cao, Yajie; Song, Yujun; Li, Lan
Abstract: The purpose of the experiment is to obtain high-efficiency microbial phosphorus dephosphorization fertilizer, increase the soluble phosphorus content of the soil, and promote plant growth. The phosphorus detoxifying bacteria in sunflower rhizosphere were studied through dilution and coating plate method, molybdenum-antimony anti-spectrophotometry, plate culture, physiological and biochemical detection. 10 strains were isolated and purified to form bright rings, D/d value is between 1.10-4.35. The quantitative analysis of the pressure showed that BX2 had the best effect in dissolving phosphorus. The available phosphorus increment was 38.59μg/mL, BX7 had the lowest phosphorus dissolving effect, and the effective phosphorus increase was only 1.77μg/mL. These strains of BX2, BX3, BX5, BX9 and BX10 have excellent phosphorus-dissolving properties, providing necessary conditions for the subsequent development of microbial fertilizer.